Citarum yang Merana dalam Pengabaian Nilai Kabuyutan Orang Sunda - Ujang Suyatman (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2021)
It is not enough to rely only on science and technology to solve the environmental crisis that is hitting the world globally today. It needs a strength in the form of moral and cultural values that the community believed so they can grow their awareness of the environment. This is the same as the Sundanese people in West Java with the crisis of Citarum river as one of the rivers that has important and strategic roles in Indonesia. The complexity of the problems that have damaged the Citarum ecosystem cannot be solved only by relying on a variety of regulations issued by the government without the community intervention. The excavation and utilization of kabuyutan and tritangtu philosophy as the Sundanese heritage of logical, ethical, and aesthetic values are expected to be one of the supports for the re-growth of public concern for the environment. Therefore, they are expected to participate in the preservation of Citarum, so that the strategic function of this river can be maintained in a sustainable manner.